Alexithymia, impulsiveness, and psychopathology in nonsuicidal self-injured adolescents - Gatta M; Dal Santo F; Rago A; Spoto A; Battistella PA (Neuropsychiatric Disease and Treatment, 2016)
Michela Gatta,1 Francesco Dal Santo,1 Alessio Rago,1 Andrea Spoto,2 Pier Antonio Battistella1 1Childhood Adolescence Family Unit, Ulss 16 – Padua University, 2Department of General Psychology, Padua University, Padova, Italy Introduction: Nonsuicidal self-injury (NSSI) is a multifaceted phenomenon and a major health issue among adolescents. A better understanding of self-injury comorbidities is crucial to improve our ability to assess, treat, and prevent NSSI.Purpose: This study aimed at analyzing some of the psychobehavioral correlates of NSSI: psychological problems, alexithymia, impulsiveness, and sociorelational aspects.Patients and methods: This was a case–control study. The clinical sample (n=33) included adolescents attending our unit for NSSI and other issues; the controls (n=79) were high-school students. Data were collected using six questionnaires: Youth Self-Report, Barratt’s Impulsiveness Scale, Toronto Alexithymia Scale, Children’s Depression Inventory, Symptom Checklist-90-R, and Child Behavior Checklist.Results: Cases scored significantly higher in all questionnaires. Habitual self-injurers scored higher on impulsiveness and alexithymia. The gesture’s repetition seems relevant to the global clinical picture: habitual self-injurers appear more likely to seek help from the sociosanitary services. We found a difference between the self-injurers’ and their parents’ awareness of the disorder.Conclusion: Habitual self-injurers show signs of having difficulty with assessing the consequences of their actions (nonplanning impulsiveness) and the inability to manage their feelings. Given the significantly higher scores found for cases than for controls on all the psychopathological scales, NSSI can be seen as a cross-category psychiatric disorder, supporting the Diagnostic and Statistical Manual of Mental Disorders decision to include it as a pathological entity in its own right. Keywords: NSSI, self-cutting, psychiatric comorbidity, impulsivity, self-report, self-harm